Chapter Repression of the future-oriented disposition of Italians by a never-ending pandemic - Di Zio, Simone (Proceedings e report, 2023)
Likely, the after-pandemic world won't be as it used. To properly imagine and build our future, we should forget the progressive growth of past times and even the concept of "normality" of pre-pandemic years is going to change inasmuch as a new social concept is coming true ("surprise free" scenarios are no longer contemplated). The disposition of Italians towards their future was surveyed with three indicators: 1) the depression rate as measured with PHQ9, a standard psychological test for clinical depression measurement; 2) the pro-activeness orientation, as measured with an 8-item psychological test; and 3) the clearness rate of own future vision, as measured with a focused, dichotomous question. The indicators have been measured through a convenience sample on Italian adults during the second half of 2021. The analysis showed that the fear of contagion and the never-ending emergency due to Covid-19 pandemic caused such a psychological awkwardness to repress the disposition of Italians towards their possible futures. The repression was harder on youngsters, living alone persons, disrupted families, and people with psychic and/or depressive symptoms. A regressive model was furtherly fit on the collected sample. It showed multiple determinants of the future repression, say, that the fear of contagion was more relevant than the contagion itself and the uncertainty about the pandemic end was as disheartening as the contagion risk for the yearning hope of a positive after-pandemic lifestyle.